A CONCEPT OF ORGANISATION OF INFORMATION SYSTEM OF TECHNICAL SUPPORT (Journal of Information Technologies in Education (ITE), 2012)
An approach to the organization of the technical support in the establishments of higher education with the help of a special information system is regarded in the article. The problems, which will be solved with the support system, are revealed. The most famous open-source systems that use the service-oriented architecture are examined. Advantages and disadvantages of the system are shown.
Keywords: HelpDesk; higher education establishments management; informatization; users support system; web- services; work process automation